Caracterização das galáxias hospedeiras de núcleos ativos identificados via espectroscopia óptica - Sousa, Raphael Gomes (2025)
In this work, we investigated the properties of host galaxies of optical AGNs using spectroscopic and photometric data from 76 054 galaxies in the SDSS (DR12), GALEX, and GZ2 surveys. We utilized the BPT and WHAN diagnostic diagrams to characterize the gas ionization source in these objects, alongside stellar mass, surface mass density, light concentration index, and Dn(4000) index to explore the relationship of these parameters with nuclear activity. We observed that [O III] luminosity is related to AGN classification, with Seyferts dominating at high luminosities and star-forming regions associated with low L[O III] values. Early-type galaxies are more common as hosts of weak AGNs, while strong AGNs are associated with both early-types and late-types, depending on the AGN type (LINER or Seyfert). The analysis of specific star formation rate (sSFR) divided galaxies into Blue Cloud (BC), Green Valley (GV), and Red Sequence (RS), revealing distinct patterns in the BPT-NII and WHAN diagrams, such as the predominance of LINERs in the RS and Seyferts in the GV. We also identified that the Dn(4000) index and concentration C are higher in the RS and lower in the BC, with the GV showing intermediate values. The Galaxy Zoo 2 survey revealed that BC galaxies are predominantly unbarred spirals, while the RS is dominated by ellipticals and lenticulars. Barred spirals are more strongly associated with AGNs in the GV. These analyses reinforce the relationship between morphology, nuclear activity, and star formation in the studied galaxies.